Nail Psoriasis in Nigerians - Enigbokan, Omolulu Adedoyin; Ogunbiyi, A O; George, A O (Explorer Front, 2025)
Background: Psoriasis is an inflammatory skin disorder that commonly affects the nails. Studies on psoriasis in our environment are very few, and data on nail abnormalities in our environment are lacking. The present study was undertaken to evaluate the frequency of nail involvement in patients with psoriasis, document the nail changes in psoriasis, and identify any existing association between some clinical parameters and nail involvement. Methods: A cross-sectional study of consecutive patients diagnosed with psoriasis at the dermatology unit of University College Hospital, Ibadan, Nigeria, between January 2015 and October 2016. Diagnoses of psoriasis were clinical and supported by histopathologic confirmation. After obtaining sociodemographic data, history of disorder, and nail symptoms, each patient had a baseline examination with special attention paid to fingernail changes, and the findings were documented. Nail involvement was compared between the two sexes and with the presence of arthritis. Severity of nail involvement was calculated using the Nail Psoriasis Severity Index Score. Results: In total, fifty-nine patients were involved in the study. Majority (78.0%) of the patients were adults with a median age of 39.0 years (interquartile range 21 – 55 years) and a male to female ratio of 0.9: 1. Psoriasis vulgaris was the most typical form of presentation in the study and nail changes were present in 51 patients (86.4%) with psoriasis. The most common nail abnormalities observed were pitting, followed by onycholysis and nail discolouration. Nail involvement was seen statistically more frequent in patients with extensive cutaneous involvement. Conclusions: Involvement of the nail is quite common in psoriasis in our environment, and at times it may be the initial manifestation. Pitting, onycholysis, and discolouration with a brownish to yellowish brown hue are the most typical nail abnormalities in patients with psoriasis in this environment. From the study, it appears that nail abnormalities tend to occur more in patients with more severe cutaneous disease.